Pressures in public sector fraud: Theoretical perspectives and implications for public sector accounting - Rahmat Aiman; Aisyah Zarkasi (Journal of Economic Resilience and Sustainable Development, 2026)
Background: Fraud in the public sector is often examined through weaknesses in internal controls and opportunities for misconduct. However, such approaches tend to overlook the structural and institutional dimensions of public bureaucracy. This study aims to reconceptualize pressure within the Fraud Triangle by integrating it with General Strain Theory, providing a deeper understanding of fraud dynamics in government organizations. Methods: A qualitative-descriptive approach using a literature review was employed to conceptually analyze pressure as a driver of public sector fraud. Secondary data from scholarly journals, books, and institutional reports were synthesized through thematic-conceptual analysis to develop a theoretical framework linking various forms of pressure to public sector accounting systems. Findings: The study identifies multiple forms of pressure in the public sector—including occupational lifestyle, institutional, structural-career, socio-cultural, and hierarchical pressures—that operate simultaneously, generating systemic strain that constrains individuals’ ability to achieve valued goals through legitimate means. Conclusion: Consequently, fraud may serve as a maladaptive coping mechanism in response to the imbalance between organizational demands and structural capacity. Effective fraud prevention thus requires a shift from detection-focused approaches to proactive strategies that mitigate structural and bureaucratic pressures as primary sources of strain. Novelty/Originality of this article: This study contributes to the public sector accounting literature by framing pressure as a governance instrument that can be managed through accounting system design. Its originality lies in emphasizing structural and institutional pressures as key determinants of fraud and highlighting the proactive role of accounting systems in mitigating systemic strain.